PICS bag adoption intensity in southern Tanzania: synergy of training and credit - Zacharia, Happiness; Feleke, Shiferaw; Nyaa, Mussa; Baributsa, Dieudonne (Frontiers in Sustainable Food Systems, 2025)
Postharvest losses in staple crops such as maize continue to undermine food security and farmers’ incomes in sub-Saharan Africa, despite the availability of safe and effective storage innovations like hermetic bags. Understanding how institutional support mechanisms influence the adoption of these technologies is critical for designing interventions that promote their widespread use. Among these mechanisms, training and access to credit play a vital role by helping to overcome knowledge gaps and financial constraints that often hinder the adoption of agricultural innovations. This study assessed how access to training and credit—individually and in combination—affects adoption intensity, measured as the proportion of maize stored in Purdue Improved Crop Storage (PICS) bags, among smallholder farmers in Tanzania. We applied a multivariate inverse probability weighting approach and Tobit model to household survey data from 908 households in two regions of Tanzania’s Southern Highlands. Results show that 45.4% of households used PICS bags for maize storage. Access to either training or credit increased PICS bag adoption intensity by 15.6 and 12.9%, respectively, compared with households that received no intervention. However, when both training and credit were provided together, adoption intensity rose by 36.6%. These findings highlight the importance of integrating training and credit to increase the proportion of maize stored in PICS bags. Efforts to promote hermetic storage technologies should include improving access to finance through both traditional and non-traditional approaches to optimize adoption intensity and further reduce postharvest losses.